PENGARUH METODE PROPRIOCEPTIVE NEUROMUSCULAR FACILITATION KEMAMPUAN SPLIT DI SMAN 2 SEPAUK - Akmal, Ali; G. Simanjuntak, Victor; Triansyah, Andika (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe problem taken in this study is "whether there is influence of Proprioceptive neuromuscular facilitation training method on split ability. The purpose of this study was to determine the effect of Proprioceptive neuromuscular facilitation training methods on split ability. The population in this study is all students in SMA Negeri 2 Sepauk class XI amounted to 40 people. Sampling in this study using propbability sampling technique is simple random sampling, which amounted to 40 people where 20 people as an experimental class and 20 people as a control class. The method used in this research is experiment with true-experimental design. Data analysis was done by manual and analysis by using t-test. Based on the result of t-test in experiment class, the value of ttest = 6.17 is bigger than T table = 1.73, it means that hypothesis is received, it means there is influence of PNF method to split ability in students of class XI SMAN 2 Sepauk. While t-test results in the control class obtained value of ttest = 0.93 smaller than the value T table = 1.73, meaning the hypothesis is not accepted, means there is no influence in the control group to split. Keywords: PNF, Split.